2013
DOI: 10.1021/ie400909u
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl Ether Carbonylation to Methyl Acetate over Nanosized Mordenites

Abstract: Nanosized mordenites were found to show significantly enhanced reaction efficiency in dimethyl ether (DME) carbonylation to methyl acetate (MA) because of a greatly facilitated diffusion process. Copper incorporation into the channels of the nanosized mordenites further promoted the reaction rate, selectivity, and stability. Moreover, upon the addition of a small amount of H 2 (5−19 vol %) to the feed gas, deactivation was suppressed during DME carbonylation, whereas the catalyst stability and rate of formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 48 publications
2
59
0
Order By: Relevance
“…[1][2][3] This process consists of two stages: DME carbonylation to methyl acetate (MA) over zeolites and MA to ethanol over copper based catalysts. [4][5][6][7][8] The rst step acquired higher activity and stability over mordenite, while the second step employed cheap copper catalysts since they possess selective hydrogenation ability. 9,10 The Cu/SiO 2 catalyst is typically used for MA hydrogenation mainly because of the non-reducible and relatively inert behavior and low cost of the catalyst, making it suitable for industrial development.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] This process consists of two stages: DME carbonylation to methyl acetate (MA) over zeolites and MA to ethanol over copper based catalysts. [4][5][6][7][8] The rst step acquired higher activity and stability over mordenite, while the second step employed cheap copper catalysts since they possess selective hydrogenation ability. 9,10 The Cu/SiO 2 catalyst is typically used for MA hydrogenation mainly because of the non-reducible and relatively inert behavior and low cost of the catalyst, making it suitable for industrial development.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, organosilanes and mono‐ or multi‐quaternary ammonium salts have been employed to introduce mesoporosity in MOR zeolite. Nearly all of the described recipes involve the addition of a mesoporogen to a synthesis mixture which contains seeds, conventional SDAs, or require complex cationic surfactants with two or more ammonium ions . There are only few reports that claim the formation of hierarchical MOR zeolite with a mono‐quaternary ammonium surfactant or aniline as a single SDA .…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] However, the zeolite catalysts suffer from rapid deactivation due to build-up of coke and large carbonaceous species within the zeolite pores. [21][22][23][24][25] The framework of mordenite contains two types of cavities: eightmembered ring (8-MR) side pockets and 12-MR main channels. It has been reported that MA synthesis takes place in the 8-MR, 26,27 whereas the 12-MR have been suggested to be responsible for the coke formation that leads to catalyst deactivation.…”
Section: Introductionmentioning
confidence: 99%